Dancing from the heart : movement, gender, and Cook Islands globalization - Alexeyeff, Kalissa (University of Hawaii Press, 2009)
This is the first study of gender, globalization, and expressive culture in the Cook Islands. It demonstrates how dance in particular plays a key role in articulating the overlapping local, regional, and transnational agendas of Cook Islanders.